Serum‐soluble PD‐L1 may be a potential diagnostic biomarker in sepsis. (16th May 2021) - Sun, Shaoqiong; Chen, Yang; Liu, Zhaojun; Tian, Rui; Liu, Jialin; Chen, Erzhen; Mao, Enqiang; Pan, Tingting; Qu, Hongping
Abstract: To investigate whether serum‐soluble PD‐L1 (sPD‐L1) is a potential biomarker for identifying sepsis. This study enrolled 64 septic patients, 29 patients with acute appendicitis, 33 patients with acute pancreatitis and 30 healthy volunteers. Sepsis was defined according to the Sepsis 3.0 criteria.[1] The associated clinical parameters were recorded, blood samples were collected on the first day of diagnosis, and serum sPD‐L1 levels were measured using enzyme‐linked immunosorbent assays. Compared with the control group, a significant increase in sPD‐L1 levels was observed in patients with sepsis (n = 64). Increased sPD‐L1 expression correlated strongly with increased clinical inflammatory values (CRP, PCT and WBC) and decreased immunological functional parameters (CD3 +, CD4 + and CD8 + cell counts). The area under the ROC curve (AUC) for sPD‐L1 in combination with the sequential organ failure assessment (SOFA) score was superior to the AUC for either sPD‐L1 or SOFA score in regard to the diagnosis of sepsis. sPD‐L1 may represent a valuable biomarker for the diagnosis of sepsis.